The mechanism of exercising the employee's right to conclude an employment contract and the formation of its content - E. M. Ofman (Правоприменение, 2024)
The subject of the research is the problems of developing an adequate, understandable for the employee and the employer mechanism of exercising the right to conclude an employment contract.The purpose of the scientific article is to confirm the hypothesis that the employment contract in modern conditions is not yet an agreement in its traditional sense, that the defect of will and/or expression of will, which the employee insists on challenging the terms of the employment contract, must be proved by himThe methodology of the study includes a systematic approach, formal-legal and logical interpretation, analysis and synthesis.The main scientific results, conclusions on the achievement of the purpose of the study. Conclusion of the employment contract is a complex, multi-motivated, multi-stage process as from the position of the content and the ways and the limits of the right of the employee and the employer. As a weak party of labor legal relations, the employee agrees to the conditions of the employment contract initiated by the employer under the fear of refusal to conclude the said contract. Using the opportunities of the Labor Code of the Russian Federation, employers determine the terms of this contract with minimal risks for themselves, of right, formation of contract content which causes the emergence of numerous lawsuits from employees about the defects of will when entering into labor legal relations, about the illegality of certain terms of the employment contract.The mechanism of concluding a labor contract by its parties, established by the labor legislation, is imperfect, and the process of forming its content is so formal that it does not allow the employee and the employer to reach a real compromise on mandatory and / or additional conditions of the contract. In the article there are proposals aimed at improving the mechanism of exercising by employees and employers of the right to conclude a contract of employment. It seems necessary to amend the Labor Code of the Russian Federation in terms of establishing a special period of appeal of an employee to the court to recognize a particular condition due to a defect of will in the conclusion of the employment contract as illegal (the beginning of the period should be defined as the day of the employment contract, since it is the day on which the employee learned or should have learned about the violation of his right); identified factors that influenced the emergence, evolution of the employee and employer will and deformed it (such factors include Only from the moment the necessary information is provided can the entitled person demand the implementation of the preferences established by labor law.